ANALISIS KESALAHAN PENGGUNAAN KONJUNGSI KOORDINATIF DALAM KARANGAN ARGUMENTASI - Helnanirma Susanti Fau; Askarman Laia; Kalvintinus Ndruru (Jurnal Education and Development, 2021)
This research is motivated by the lack of knowledge of class X students of SMA Negeri 1 Telukdalam about the proper use of coordinating conjunctions. This study aims to analyze errors in the use of coordinating conjunctions (addition, selection, correction, affirmation, error, sorting, equating, inferring) in an argumentative essay. The source the data in this study is the argumentative essay of class X students SMA Negeri 1 Telukdalam. The method used in this study is a descriptive method with a qualitative approach. Data collection technique in this research is documentation technique. The researcher came to the research site, submitted a research permit and a set of proposals, visited a room and gave an understanding along with an example of an argumentative essay. Next, the researcher assigned the students to write an argumentative essay, after the researcher did the documentation by taking photos and collecting the results of the student's argumentative essay. Then the researcher classifies the errors in the use coordinating conjunctions contained in the argumentative essay and identifies the forms errors in the use of coordinating conjunctions. The research findings obtained were errors in the use of coordinating conjunctions, namely (1) conjunctions which stated the addition of conjunctions and and and, (2) conjunctions which stated selection, namely conjunctions or (3) conjunctions which stated namely, while and but conjunctions. This is indicated by the number of students' mistakes in using coordinating conjunctions in argumentative essays due to the lack of students' knowledge about the proper use of coordinating conjunctions and not being able to use the correct use of coordinating conjunctions. Based on this research, the researcher suggests that teachers improve students' understanding of the proper use of coordinating conjunctions in writing argumentative essays.